Communicative Situations and Scenarios across Socio-technical Contexts of In-house Translation Departments at Industrial Enterprises - E. S. Krasnopeyeva; S. S. Kraeva (Научный диалог)
This article presents a descriptive study based on a series of interviews (11 h 37 min) with translators at seven different enterprises located in the Chelyabinsk region, Russia. It focuses on translation decision-making processes in hybrid environments combining face-to-face and mediated interaction. The objective of this study is to identify the differences and similarities in the communicative situations described by the translators, and to establish categories to describe the ways socio-technical contexts affect the translators’ expert actions. A review of studies that apply actor-network theory (ANT) to study translation workflows across diverse production contexts is presented. Drawing on Skopos theory and ANT, the authors identify two types of scenarios in translators’ interactions with a variety of actors, including technologies that influence translation activity during skopos specification, target-text production, and quality control. The authors argue that the principal aim of the translation departments’ individual information infrastructure is to mitigate uncertainty in the decision-making process. This study demonstrates how translators augment their work environment to optimize expert performance using technological and organizational solutions. Possible ways to enhance the efficiency of translation departments at industrial enterprises are discussed.